PP.17.13: COMPARISON OF MOBIL-O-GRAPH AND SPACELABS 90217 AMBULATORY MONITORING DEVICES IN HEALTHY VOLUNTEERS. (June 2015) - Imprialos, K.; Sarafidis, P.; Lazaridis, A.; Georgianos, P.; Avranas, K.; Doumas, M.; Protogerou, A.; Nasothimiou, E.; Athyros, V.; Karagiannis, A.
Abstract : Objective: Mobil-O-Graph and Spacelabs 90217 are two validated devices for ambulatory blood pressure (BP) monitoring. However, currently only one small study has compared BP values recorded from these devices. The present study compared the values of systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) measured by both devices under ambulatory conditions in healthy volunteers. Design and method: We studied 40 healthy volunteers aged 18–30 years old, who were randomized in two groups. In both groups, a 6-hour ambulatory measurement was performed starting from 9:00 AM. In group A, the Spacelabs device was applied on the dominant arm and the Mobil-O-Graph device was applied on the non-dominant arm for the first 3 hours, followed by a reverse positioning of the devices for the following 3 hours. In group B, the same procedure was followed but the Mobil-O-Graph device was applied on the dominant arm and the Spacelabs device was applied on the non-dominant arm for the first 3 hours and vice versa. The two devices measured BP simultaneously every 20 min. Results: The mean SBP levels recorded with the Mobil-O-Graph did not differ significantly from those derived from the Spacelabs device (Mobil-O-Graph: 118.3 ± 11.0 mmHg, Spacelabs: 117.9 ± 11.4 mmHg, p = 0.864). The mean values of DBP recorded with Mobil-O-Graph were higher only by 1 mmHg and the difference was not significant (Mobil-O-Graph: 74.7 ± 8.0 mmHg, Spacelabs: 73.7 ± 7.4 mmHg, p = 0.571). However, the mean values of MAP differed significantly between the two devices (Mobil-O-Graph: 94.7 ± 8.7 mmHg, Spacelabs: 87.9 ± 7.9 mmHg, p = 0.001). All 3 parameters estimated by Mobil-O-Graph showed highly significant (p < 0.001) correlations with the relevant measurements of Spacelabs (SBP, r = 0.933; DBP, r = 0.953; MAP, r = 0.955). The Bland-Altman Plots showed acceptable agreement between the two devices for SBP and DBP. Conclusions: The Mobil-O-Graph and Spacelabs devices did not differ significantly in terms of SBP and DBP measurements under ambulatory conditions. However, a significant difference in the values of MAP between the two devices was observed. Whether this observation could be attributed to a difference in the internal algorithm of both devices remains unknown.